1999
DOI: 10.1046/j.1365-2788.1999.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse diagnostic and behavioural patterns amongst people with a dual diagnosis

Abstract: People who have both an intellectual disability and a mental illness diagnosis are gaining more attention in the mental health and developmental disabilities service systems. This interest is partly because of the challenging behaviours and the complexities of the problems in this population. The present study analyses the diagnoses, behaviour problems and demographic characteristics of a group of people with a dual diagnosis to determine if specific patterns are evident which distinguish this set of subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…There is little doubt that for some people with learning disabilities who challenge a co-morbidity between mental illness and challenging behaviour occurs (Rush & Frances 2000, IASSID 2001, Ross & Oliver 2002. Many people with learning disabilities present mental health problems through displaying challenging behaviours (Dudley et al 1999) and this is referred to as atypical presentation of mental illness; or conversely challenging behaviour may act to socially isolate an individual or cause them personal distress, which contributes to the development of a mental health problem. The difficulty is exasperated as mental illnesses can be 'cloaked' or hidden by the person's learning disabilities and behaviours; a concept referred to as 'diagnostic overshadowing' (Reiss et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt that for some people with learning disabilities who challenge a co-morbidity between mental illness and challenging behaviour occurs (Rush & Frances 2000, IASSID 2001, Ross & Oliver 2002. Many people with learning disabilities present mental health problems through displaying challenging behaviours (Dudley et al 1999) and this is referred to as atypical presentation of mental illness; or conversely challenging behaviour may act to socially isolate an individual or cause them personal distress, which contributes to the development of a mental health problem. The difficulty is exasperated as mental illnesses can be 'cloaked' or hidden by the person's learning disabilities and behaviours; a concept referred to as 'diagnostic overshadowing' (Reiss et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…ED in this population therefore seems to be diagnosed as characteristics of a behavioural profile (e.g. Dudley et al, 1999;Reid & Ballinger, 1995) or as a cluster of symptoms which achieve a diagnosis (e.g. Bouras & Drummond, 1992;Felstrom et al, 2005).…”
Section: Treatment Of Ed In Ldmentioning
confidence: 99%
“…Since ED are associated with more severe LD (Danford & Huber, 1982;Reid et al, 1978), multiple physical and mental disabilities (Dudley et al, 1999), lower adaptive behaviour (Dudley et al, 1999) and poorer social and verbal skills (Matson et al, 2006), it is possible that some ED in people with LD may be manifestations of poor functioning, physical or mental health problems. Holt, Bouras, and Watson (1988) report that rather than evidencing AN, the onset of food refusal in a client with Down's syndrome coincided with a throat infection and admission to hospital.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…(2006) found an association between affective symptoms and self‐injury and aggression; screaming and destructive behaviours appeared to be associated with autistic type features. Dudley et al. (1999) identified six different behavioural patterns in a sample of 940 participants using factor analytic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hemmings et al (2006) found an association between affective symptoms and self-injury and aggression; screaming and destructive behaviours appeared to be associated with autistic type features. Dudley et al (1999) identified six different behavioural patterns in a sample of 940 participants using factor analytic methods. These were as follows: aggressive ⁄ disturbing behaviour, with-drawal ⁄ asocial behaviour, inappropriate behaviour, sociopathic characteristics, suicidal or absconding and pica.…”
Section: Introductionmentioning
confidence: 99%